2020
DOI: 10.1038/s41467-020-16504-1
|View full text |Cite
|
Sign up to set email alerts
|

A network of RNA-binding proteins controls translation efficiency to activate anaerobic metabolism

Abstract: Protein expression evolves under greater evolutionary constraint than mRNA levels, and translation efficiency represents a primary determinant of protein levels during stimuli adaptation. This raises the question as to the translatome remodelers that titrate protein output from mRNA populations. Here, we uncover a network of RNA-binding proteins (RBPs) that enhances the translation efficiency of glycolytic proteins in cells responding to oxygen deprivation. A system-wide proteomic survey of translational engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 125 publications
(173 reference statements)
1
61
0
Order By: Relevance
“…Furthermore, pSILAC allows us to exclude newly synthesized peptides as a confounding signal during analysis of the factors that constitute the machinery (and not the products) of protein synthesis. Using the ratio of protein abundance in the polysome-to-ribosome-free fractions as a primary readout as previously established (Balukoff et al, 2020;Ho et al, 2018Ho et al, , 2020, MATRIX revealed substantial reorganization of the translation machinery, confirming downregulation of eIF4E-dependent translation (Figure 5B, blue) and an overall decrease in ribosomal engagement (Figure 5C). Alternatively, the translation elongation factor eEF1ε1, which participates in tRNA charging, demonstrated the highest increase in translational engagement out of known detected canonical translation factors (Figure 5B, red).…”
Section: Rocaglates Globally Reprogram the Protein Synthesis Machinerysupporting
confidence: 68%
See 2 more Smart Citations
“…Furthermore, pSILAC allows us to exclude newly synthesized peptides as a confounding signal during analysis of the factors that constitute the machinery (and not the products) of protein synthesis. Using the ratio of protein abundance in the polysome-to-ribosome-free fractions as a primary readout as previously established (Balukoff et al, 2020;Ho et al, 2018Ho et al, , 2020, MATRIX revealed substantial reorganization of the translation machinery, confirming downregulation of eIF4E-dependent translation (Figure 5B, blue) and an overall decrease in ribosomal engagement (Figure 5C). Alternatively, the translation elongation factor eEF1ε1, which participates in tRNA charging, demonstrated the highest increase in translational engagement out of known detected canonical translation factors (Figure 5B, red).…”
Section: Rocaglates Globally Reprogram the Protein Synthesis Machinerysupporting
confidence: 68%
“…As the most energy-consuming cellular investment (Li et al, 2014), the complexity of eukaryotic protein synthesis machinery (Jackson et al, 2010) provides intricate, precise control over protein production during cellular state transition (Ho and Lee, 2016;Liu et al, 2016). Accumulating evidence (Cai et al, 2020;de la Parra et al, 2018;Landon et al, 2014;Lee et al, 2015;Liu et al, 2016;Schwanha ¨usser et al, 2011;Vogel and Marcotte, 2012), including ours (Balukoff et al, 2020;Ho et al, , 2018Ho et al, , 2020, demonstrates the predominance of translation efficiency (TE) and translation machinery adaptations over transcript-level fluctuations in determining protein output (translatome) and phenotype in human cells responding to physiologic stimuli. In this study, we address whether this paradigm also applies to therapeutic interventions, especially those traditionally thought to elicit translational inhibition as their sole mode of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding beyond this traditional target-specific strategy, recent developments in high throughput technologies (discussed below) have provided the ability to dissect the intricate relationships between translatome remodelers and their target mRNAs from a systems-level perspective (Achsel & Bagni, 2016;Ho, Balukoff, et al, 2020). This unbiased approach has revealed key principles of post-transcriptional regulation, including the fresh insight that in response to different stresses, translatome remodelers are dynamically repurposed and reorganized into unique networks, each targeting a distinct but overlapping selection of mRNAs to fully activate adaptive cellular pathways (Hogan et al, 2008;Mukherjee et al, 2019;Quattrone & Dassi, 2019;Sternburg & Karginov, 2020).…”
Section: High-throughput Strategies Reveal Systems-level Principles Of Translatome Remodelingmentioning
confidence: 99%
“…Recently, various RBP-related mechanisms in cancer onset and progression have been clarified, including genomic alterations, transcriptional and post-transcriptional control, and posttranslational modifications [ 5 ]. In addition, RBPs directly or indirectly affected oncogenic and tumour-suppressive signalling pathways [ 6 ]. However, only a few RBPs have been completely studied and identified as vital players in human cancers.…”
Section: Introductionmentioning
confidence: 99%